1976
DOI: 10.1152/jappl.1976.41.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Physiological aging of champion runners

Abstract: The physiological adjustments to aerobic work (5.6 km/h, up a 9% grade) and to exhausting treadmill work of former champion middle-distance runners were determined in 1971, at ages 47-68 yr, 25-43 yr after their competitive careers in track. In the resting state the former athletes as a group are very much like nonathletes of the same ages. Efficiency in the aerobic walk was the same in both groups and did not change with age in either, but the former athletes on the average performed the walk with less strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 0 publications
4
22
0
1
Order By: Relevance
“…AVO 2 of 10 ml/kg/min is only a modest effort for young, healthy people, but for an elderly user, it is a large fraction ofVO 2 max. Several cross-sectional studies suggest thatVO 2 max declines approximately 0.58 ml O 2 /kg/min/year in older populations (people 55-85) [10][11][12][13][14]. Consider a typical 85-year old, community dwelling woman that has aVO 2 max of approximately 15 ml/ kg/min [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AVO 2 of 10 ml/kg/min is only a modest effort for young, healthy people, but for an elderly user, it is a large fraction ofVO 2 max. Several cross-sectional studies suggest thatVO 2 max declines approximately 0.58 ml O 2 /kg/min/year in older populations (people 55-85) [10][11][12][13][14]. Consider a typical 85-year old, community dwelling woman that has aVO 2 max of approximately 15 ml/ kg/min [14].…”
Section: Discussionmentioning
confidence: 99%
“…Many elderly people report that walkers are difficult to use [3,4]. A major difficulty is that the metabolic cost of ambulation with a walker is greatly elevated [5][6][7][8][9] combined with the diminished aerobic capacity associated with aging [10][11][12][13][14]. In this study, we quantified the major reasons why walker-assisted gait is so expensive.…”
mentioning
confidence: 99%
“…Generally, the functional capacity of the cardiovascular system declines with aging, resulting in a decrease in • maximal oxygen uptake (VO2max) (Astrand, 1960;Kasch et al, 1985;Dill et al, 1967;Robinson et al, 1976). The…”
Section: Introductionmentioning
confidence: 99%
“…11 The results of our study con®rm that the prevention of weight gain depends on continued physical activity rather than on the genetic predisposition. 24 The body fat percentage in middle-aged and older athletes is higher than in young athletes, although markedly less than in age-matched sedentary controls, showing that body fat increased by $ 2% over 10 y even in those athletes who remained highly competitive. 5 Our study suggests that most former athletes (59.3%) tend to gain weight during 15 ± 30 y after their sports career is discontinued (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…In a study of former elite middle-distance runners, the mean weight gain was 7.1 kg over $ 22 y after they stopped training. 24 Sarna et al 16 reported the highest weight gain in power sports athletes 28.5 AE 9.8 30.9 AE 5.6 27.1 AE 7.0* 22.5 AE 6.1*** *P`0.05; **P`0.01; ***P`0.001, values statistically signi®cantly different from`constant weight'. Table 3 Age-, physical activity-and weight-adjusted ORs and 95% CI for hypertension, abdominal fat distribution pattern and hyperlipidemias in different weight-change groups compared with the`constant weight' group Hypertension WHR !…”
Section: Discussionmentioning
confidence: 98%